أثر حل المجالس الشعبية المحلية في التشريع الجزائري - بوزنة, بوبكر; السعيد غندير, السعيد (University of Eloued جامعة الوادي, 2020)
تختمف أنواع الرقابة الوصائية عمى المجالس المحمية المنتخبة بين رقابة عمى الأشخاص ورقابة عمى الأعمال واخطر أنواع الرقابة ىي الرقابة عمى الييئة ككل المتمثمة في إيقاف و حل المجمس الشعبي المحمي, التي انحصرت في حل المجمس فقط, والذي يعني إنياء الوجود القانوني لممجمس المحمي قبل انتياء المدة القانونية لمعيدة, مع بقاء الشخصية المعنوية لمولاية أو البمدية قائمة,ىذا الإج ا رء الذي يرتب آثا ا ر قانونية بالغة الأىمية, يمجأ لياتو الرقابة في حالة توفر الأسباب التي نص عمييا المشرع حص ا ر في قانوني الولاية والبمدية ويتم حل المجمس بمرسوم رئاسي بناء عمى تقرير من وزير الداخمية, الذي بدوره يتمقى تقريره من الوالي. يمجأ بعدىا لتجديد .07/ 10 و 12 - المجالس المحمية وفقا للأحكام التي جاء بيا القانونين رقمي 11.The types of guardianship control over the elected local councils differ between the supervision of people and the control of work and the most dangerous types of control are the control of the body as a whole represented in stopping and dissolving the local people's council, which was limited to dissolving the council only, which means ending the legalpresence of the local council before the end of the legal period This procedure, which has very important legal implications, will be followed by oversight if the reasons stipulated by the legislator are provided exclusively in state and municipal laws and the council is dissolved by presidential decree based on a report from the Minister of Interior, who in turn He receives his report from the Viceroy. Then, he shall resort to the renewal of the local councils in accordance with the provisions .stipulated in the laws Nos. 10-11 and 07/12.
مدكرة ماستر
Keywords: -الرقابة الوصائية- 2 المجالس الشعبية المحمية المنتخبة 3- الرقابة عمى الييئة 4-الحل 5-آثار الحل.; 1-supervision of guardianship 2- local people's councils 3- control of the commission-4- dispersal / dismantling of the elected council.5- Effects of dispersion / dismantling.